You can find the value of ϕ = 2 1 + 5 by iteration. Start with x 1 = 2 and x 2 = 1 + x 1 1 = 1 . 5 and for the ( n + 1 ) th iteration:
x n + 1 = 1 + x n 1
For large n , we can express the error term as ∣ e n ∣ = ∣ x n − ϕ ∣ . It can be shown that n → ∞ lim ∣ e n ∣ d ∣ e n + 1 ∣ = c a − b , where a , b , c do not have common divisors. Find a + b + c + d .
If you like this problem, try Golden Iterations II .
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
We can easily see that x n = F n + 1 F n + 2 where F n is the n t h Fibonacci Number
So, ∣ e n ∣ = F n + 1 ϕ F n + 1 − F n + 2
Now, using Binet's Formula we get
e n = ϕ 2 n + 3 + ( − 1 ) n ϕ 1 + ϕ 2
Putting this expression in the limit, we can see that d = 1 for the limit to exist and hence, evaluating the limit leads us to the answer which is ϕ 2 1
So, ϕ 2 1 = 2 3 − 5 makes our answer 1 1
3 + 5 + 2 + 2 = 12 not 11
By definition, x n can be written as 1 + x n − 1 1 ; now, since ϕ is solution of x = 1 + x − 1 , we can rewrite it as ϕ = x n = 1 + x n 1 . So, ∣ e n ∣ = ∣ x n − 1 1 − x n 1 ∣ . Now we can calculate the limit, writing everything in function of x n : if you have not made mistakes, you will end up with ∣ x n + 1 ∣ ∣ 1 + x n 1 − x n ∣ 1 − d . Note that 1 + x n 1 − x n , for n → ∞ ,since x n = ϕ , is equal to 0: putting d = 1 , the limit exists and it's not 0, but tends to 1 + ϕ 1 , which is equal to 2 3 − 5 . In the end, the answer is 3 + 5 + 2 + 1 = 1 1 .
Problem Loading...
Note Loading...
Set Loading...
Note that x n + 1 = 1 + x n 1 , and ϕ = 1 + ϕ 1 . Hence ∣ e n ∣ d ∣ e n + 1 ∣ = ∣ x n − ϕ ∣ d ∣ 1 + x n 1 − ( 1 + ϕ 1 ) ∣ . Set f ( x ) = 1 + 1 / x and d = 1 . Then the expression becomes ∣ ∣ ∣ x n − ϕ f ( x n ) − f ( ϕ ) ∣ ∣ ∣ Since lim n → ∞ x n = ϕ it becomes lim x → ϕ ∣ ∣ ∣ x − ϕ f ( x ) − f ( ϕ ) ∣ ∣ ∣ which is ∣ f ′ ( ϕ ) ∣ , which is ϕ 2 1 , which evaluates to 2 3 − 5 which gives the answer of 11.